Solidaritas Antar Pegawai untuk Mengatasi Beban Kerja dan Ketercapaian Kerja - Vika Shafira Permatasari; Ika Korika Swasti (Journal of Management and Bussines (JOMB), 2023)
This study aims to determine and analyze the impact of workload and solidarity among employees on work achievement. This research uses qualitative methods and a case study approach. The main techniques in collecting data are observation, in-depth interviews and documentation. The results of the study show that a strong sense of solidarity or employees, a family atmosphere and a work environment for refreshing can motivate employees. Targets can still be achieved with cooperation and family conditions. In conclusion, high workload and changes in the organizational environment due to the pandemic have an impact on workload. With solidarity between employees at the BRI Trawas Unit through cooperation and the support of all existing elements, the BRI Trawas Unit was able to achieve a goal of making a growing and healthy bank with loyal employees and customers. Keywords: Workload, Work Achievement, Solidarity